2006
DOI: 10.1534/genetics.106.055491
|View full text |Cite
|
Sign up to set email alerts
|

New Alleles of SIR2 Define Cell-Cycle-Specific Silencing Functions

Abstract: The establishment of transcriptional silencing in yeast requires cell-cycle progression, but the nature of this requirement is unknown. Sir2 is a protein deacetylase that is required for gene silencing in yeast. We have used temperature-sensitive alleles of the SIR2 gene to assess Sir2's contribution to silencing as a function of the cell cycle. When examined in vivo, these conditional alleles fall into two classes: one class exhibits a loss of silencing when raised to the nonpermissive temperature regardless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 66 publications
(94 reference statements)
1
22
0
Order By: Relevance
“…Their mutants fell into two classes. One group had defects in deacetylase activity and the other had defects in binding to Sir4 (Matecic et al 2006). Similar to the sir2-276 mutant described here, they found that the deacetylase-defective mutants lost silencing rapidly when raised to the nonpermissive temperature.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Their mutants fell into two classes. One group had defects in deacetylase activity and the other had defects in binding to Sir4 (Matecic et al 2006). Similar to the sir2-276 mutant described here, they found that the deacetylase-defective mutants lost silencing rapidly when raised to the nonpermissive temperature.…”
Section: Discussionsupporting
confidence: 77%
“…Apparently, more Sir2 activity is required in vivo at 37°than at 25°. Holmes and colleagues recently described several sir2 ts mutants generated by error-prone mutagenesis (Matecic et al 2006;Hickman et al 2007). All but one of these mutants had multiple amino acid changes.…”
Section: Discussionmentioning
confidence: 99%
“…Note that when HML␣ is derepressed in a MATa strain (e.g., by disrupting the SIR genes), the a1 and ␣2 proteins form a complex that negatively regulates the expression of ␣1 and ␣2 (16,26,35). However, ␣1 mRNA is detectable in such a strain, especially when methods with high sensitivity like qRT-PCR are used (9,23,40). Matecic et al has demonstrated that the transcriptional state of HML could be examined quantitatively by measuring the abundance of HML␣1 message (23).…”
Section: Resultsmentioning
confidence: 99%
“…However, ␣1 mRNA is detectable in such a strain, especially when methods with high sensitivity like qRT-PCR are used (9,23,40). Matecic et al has demonstrated that the transcriptional state of HML could be examined quantitatively by measuring the abundance of HML␣1 message (23). As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, a trans-activator is better able to activate a gene repressed by telomeric heterochromatin when expressed at the start of M-phase than it is in G 1 (Aparicio and Gottschling 1994). In addition, specific conditional alleles of the SIR2 silencing factor gene cause an M-phase-specific silencing defect (Matecic et al 2006). Most significantly, the establishment of silencing in yeast requires progression through the cell cycle (Miller and Nasmyth 1984;Fox et al 1997;Kirchmaier and Rine 2001;Li et al 2001;Lau et al 2002;Kirchmaier and Rine 2006).…”
mentioning
confidence: 99%